2019
DOI: 10.1186/s12911-019-0918-5
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven approach to predicting diabetes and cardiovascular disease with machine learning

Abstract: BackgroundDiabetes and cardiovascular disease are two of the main causes of death in the United States. Identifying and predicting these diseases in patients is the first step towards stopping their progression. We evaluate the capabilities of machine learning models in detecting at-risk patients using survey data (and laboratory results), and identify key variables within the data contributing to these diseases among the patients.MethodsOur research explores data-driven approaches which utilize supervised mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
189
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(198 citation statements)
references
References 32 publications
6
189
0
3
Order By: Relevance
“…In contrast to traditional methods, machine learning can learn the nonlinear interactions iteratively from large amounts of data using computer algorithms 13 , which have been applied in various fields, such as disease risk assessment and prediction 14,15 . Recent research shows that machine learning methods can describe patients' characteristics and identify patients at risk of developing T2DM 16,17 . A study illustrated the performance of support vector machine for detecting persons with diabetes and pre-diabetes 18 .…”
mentioning
confidence: 99%
“…In contrast to traditional methods, machine learning can learn the nonlinear interactions iteratively from large amounts of data using computer algorithms 13 , which have been applied in various fields, such as disease risk assessment and prediction 14,15 . Recent research shows that machine learning methods can describe patients' characteristics and identify patients at risk of developing T2DM 16,17 . A study illustrated the performance of support vector machine for detecting persons with diabetes and pre-diabetes 18 .…”
mentioning
confidence: 99%
“…The XGBoost model has achieved excellent performance in many fields of medical research. [23][24][25][26] Currently, no researchers have used the XGBoost model to predict the time series data of human brucellosis.…”
mentioning
confidence: 99%
“…The data analysis driven by ML is a quite new approach in medical care and complementary diagnosis (Heinrichs and Eickhoff 2020 ; Sidey-Gibbons and Sidey-Gibbons 2019 ; Watson et al 2019 ); however, in the last years, several studies have reported the use of ML with image data or clinical specimens (blood, stool, urine) to help in diagnose cancer (Kourou et al 2015 ; Podnar et al 2019 ; Salod and Singh 2019 ; Wu et al 2019 ), diabetes and cardiovascular disease (Dinh et al 2019 ; Kavakiotis et al 2017 ; Shameer et al 2018 ) among other conditions (Ayling et al 2019 ; Gunčar et al 2018 ; Poostchi et al 2018 ; Ullah et al 2019 ). Considering the infective diseases, ML techniques were used to identify dengue (Hair et al 2019 ), bacterial infections (Rawson et al 2019 ) and, more recently, COVID-19 (Banerjee et al 2020 ; Brinati et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%